PENGARUH PERTUMBUHAN LABA, STRUKTUR MODAL, LIKUIDITAS DAN KOMISARIS INDEPENDEN TERHADAP KUALITAS LABA DENGAN KOMISARIS INDEPENDEN DIMODERASI OLEH KOMPETENSI KOMISARIS INDEPENDEN (Studi pada Perusahaan Manufaktur yang terdaftar pada Bursa Efek Indonesia pe - Kartika Aulia Zein; Raja Adri Satriawan Surya; Alfiati Silfi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2016)
This study aimed to examine whether (1) the effect of earnings growth earnings quality, (2) the effect of the capital structure of the profit on the quality of earnings (3) the effect of liquidity on the quality of earnings and (4) the influence of independent directors to be moderated by the competence of independent directors on the quality of earnings on companies listed in the Indonesia Stock Exchange. Population of this research are manufacturing companies listed in Indonesia Stock Exchange (BEI) in 2013 until 2014. The research proves that (1) earnings growth positive significant effect on the quality of earnings with a significant level of 0.025, (2) the capital structure of a significant negative effect on the quality of earnings with a significant level of 0.200, (3) liquidity significant positive effect on the quality of earnings with significant level of 0.100 and (4) an independent commissioners significant negative effect on the quality of earnings with competence moderated by an independent commissioner with a significant level of 0.000Keywords: Quality of earnings, capital structure, profit growth, liquidity and Independent commissioner